Anti-Inflammatory Effects of an Extract of Polygonum hydropiper Stalks on 2,4,6-Trinitrobenzenesulphonic Acid-Induced Intestinal Inflammation in Rats by Inhibiting the NF-κB Pathway - Wei Zhang; Yingni Pan; Shouhe Qu; Dongmei Wang; Song Cheng; Xiaoqiu Liu (Mediators of Inflammation)
The stalks of Polygonum hydropiper L. (PHL) have been traditionally used in clinical practice for thousands of years in China to treat various inflammatory diseases. However, little research has been conducted to investigate the anti-inflammatory effects of PHL on TNBS-induced intestinal inflammation in rats. The aim of the present study was to investigate the anti-inflammatory effects and to explain the underlying mechanism of PHL on TNBS-induced intestinal inflammation in rats. PHL (125, 250, and 500 mg/kg) was given for 7 consecutive days to rats with intestinal inflammation induced by TNBS. Oral administration of an aqueous extract of a high dose of PHL (H-PHL) significantly improved TNBS-induced symptoms such as the macroscopic score and histological examination. H-PHL treatment significantly ameliorated the activity of MPO and improved the GSH content. In addition, there was a downregulation of the TNBS-induced increase in the activity of iNOS and levels of Cox-2, TNF-α, and IL-1β while the protein expression of NF-κB was significantly unregulated after administration of H-PHL. The present findings suggested that H-PHL has a protective effect on experimental intestinal inflammation in rats and its anti-inflammatory effects are closely related to inhibition of NF-κB signal pathways.